Acute Treatment of Migraine - ÖZTÜRK, Vesile (Noro Psikiyatr Ars, 2013)
Migraine is one of the most frequent disabling neurological conditions with a major impact on the patient’s quality of life. Migraine has been described as a chronic disorder that characterized with attacks. Attacks are characterized by moderate–severe, often unilateral, pulsating headache attacks, typically lasting 4 to 72 hours. Migraine remains underdiagnosed and undertreated despite advances in the understanding of its pathophysiology. This article reviews management of migraine acute pharmacological treatment. Currently, for the acute treatment of migraine attacks, non-steroidal anti-inflammatory drugs (NSAIDs) and triptans (serotonin 5HT1B/1D receptor agonists) are recommended. Before intake of NSAID and triptans, metoclopramide or domperidone is useful. In very severe attacks, subcutaneous sumatriptan is first choice. The patient should be treated early in the attack, use an adequate dose and formulation of a medication. Ideally, acute therapy should be restricted to no more than 2 to 3 days per week to avoid medication overuse.